2020
DOI: 10.1155/2020/2958635
|View full text |Cite
|
Sign up to set email alerts
|

Sicca Symptoms in Parkinson’s Disease: Association with Other Nonmotor Symptoms and Health-Related Quality of Life

Abstract: Background. Frequently used nonmotor scales do not cover all aspects of dysautonomia in Parkinson’s disease (PD). This study explores the association between autonomic symptoms and sicca symptoms with other nonmotor symptoms and health-related quality of life (QoL) in PD. Methods. Autonomic symptoms (Survey of Autonomic Symptoms, SASs), motor function (Movement Disorder Society-sponsored revision of the Unified Parkinson’s Disease Rating Scale III, MDS-UPDRS III), nonmotor symptoms (nonmotor symptoms questionn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 32 publications
(40 reference statements)
0
10
0
Order By: Relevance
“…In the last decade, the influence of non-motor symptoms was extensively studied [ 41 ]. However, even during the last few years, several neglected non-motor symptoms have emerged or found new spotlights [ 26 , 40 , 42 ]. Our results support the role of alexithymia as a non-motor symptom contributing to impaired quality of life in PD.…”
Section: Discussionmentioning
confidence: 99%
“…In the last decade, the influence of non-motor symptoms was extensively studied [ 41 ]. However, even during the last few years, several neglected non-motor symptoms have emerged or found new spotlights [ 26 , 40 , 42 ]. Our results support the role of alexithymia as a non-motor symptom contributing to impaired quality of life in PD.…”
Section: Discussionmentioning
confidence: 99%
“…However, in another study, 50% of the PD patients were reported to have xerostomia accompanied by hyposalivation [ 22 ]. It was reported by other researchers that an even higher prevalence of 69% PD patients had sicca symptoms (xerostomia and dry eyes), which might be caused by anti-PD medications or antidepressant drugs [ 23 ]. Our study showed that 59.14% of the total PD patients had dry mouth, 57.89% in M-PD and 60.44% in FM-PD, respectively, in accordance with other reports.…”
Section: Discussionmentioning
confidence: 99%
“…However, there was no significant difference between men and women. Dry mouth contributes to both caries and periodontal disease, influences not only oral health but also general health-related quality of life (QoL), and is thought to be closely associated with malnutrition in PD patients [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cardiovascular alterations can affect approximately 80% of PD patients and can worsen the progression of the disease, increasing the risk of death [17,29,65]. The most frequent clinical manifestation of cardiac autonomic failure in PD is OH [66].…”
Section: Clinical Manifestationsmentioning
confidence: 99%
“…Therefore, it is suggested that both cardiac sympathetic denervation and parasympathetic dysfunction can occur concurrently [16]. Cardiovascular disorders have been detected in approximately 80% of PD patients [17], with OH being the most common cardiac-related autonomic dysfunction (30-40% of cases) [15]. Investigating the cardiac condition in PD could provide a more accurate (and earlier) in vivo diagnosis.…”
Section: Introductionmentioning
confidence: 99%